Barnacle cyprid motility and distribution in the water column as an indicator of the settlement-inhibiting potential of nontoxic antifouling chemistries - Maleschlijski, Stojan; Bauer, Stella; Fino, Alessio Di; Sendra, Gonzalo H.; Clare, Anthony S.; Rosenhahn, Axel (Biofouling, 2014)
Testing of new coatings to control fouling frequently involves single-species laboratory bioassays. Barnacle cyprids are among the most widely used model organisms in marine biofouling research, and surfaces that inhibit their settlement are considered to be promising candidates for new coating concepts. An analysis of motility parameters (mean velocity and swimming area coefficient) and distribution of cyprids of Balanus amphitrite in different swimming regions in the vicinity of model surfaces (self-assembled monolayers) is presented. The data are correlated with the settlement preferences of cyprids on these surfaces. Cyprids were predominantly found in interfacial regions and the transition frequencies between swimming regions of different depths were determined.